Information System and Motivation Determinants of Lecturer Research Performance: Perception of Lecturers at the Semarang Polytechnic - Astyandini, Budi; Pramono, Suwito Eko; Pudjiastuti, RR Sri Endang; Yulianto, Arief (Journal of Ecohumanism, 2024)
The research performance of midwifery lecturers is an important assessment. The purpose of the study was to determine the influence of information systems, good university governance, supervisors, and motivation on performance. Semarang Polytechnic is the largest polytechnic in Indonesia consisting of Semarang, Kendal, Purwokerto, Magelang, and Blora campuses. Google Form questionnaire data collection. Data analysis with multiple linear regression research variables information systems, Good University Governance, Supervision and Motivation, and Kinrja. The results of the study showed that governance, supervision, and motivation affected research performance. Information systems partially do not affect the performance of the study. At the same time, the information system, Good University governance, supervision, and motivation simultaneously affect the research performance factors of research lecturers contribute to the literature on the research performance of lecturers in the midwifery department as a consideration for the director to take a policy on the research performance of lecturers Polytechnic Leadership must create an information system g easy to use, complete, and connected one lecturer performance report makes it easier for lecturers to prepare administration of research reports so that they are motivated to conduct quality research.